2017
DOI: 10.3390/ijerph14121566
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depressive Symptoms and Child Behavior among Mexican Women and Their Children

Abstract: Over 50% of mothers in rural Mexico have high depressive symptoms, and their children's health and development are likely to be negatively affected. A critical question is whether children vary in their vulnerability to the effects of high maternal depressive symptoms according to their indigenous ethnicity, maternal education, or household wealth. Our sample included 4442 mothers and 5503 children from an evaluation of Mexico's social welfare program. Maternal depressive symptoms were assessed using the Cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 79 publications
(84 reference statements)
1
5
0
2
Order By: Relevance
“…Maternal PPD symptoms (EPDS !10) were also found to significantly affect Total Behaviour Problems (b ¼ 0.670; p < 0.001), Internalizing Problems (b ¼ 0.172; p ¼ 0.005), and Externalizing Problems (b ¼ 0.232; p < 0.001) scores in children evaluated with the Child Behavior Checklist (CBCL) at 3 months postpartum 30 . A similar association was found between PPD symptoms and child behavioral outcomes in another study, with significant associations between PPD symptoms as measured by the CES-D and child behavioral problems as measured by the Behavior Problems Index (BPI; p < 0.0001) 38 . Two studies reported non-statistically significant associations between PPD symptoms and outcomes in children, such as infant development (cognitive, language, and motor) at 18 months 29 and cognitive function at 24 months of age 74 .…”
Section: The Humanistic Burden Of Postpartum Depressionsupporting
confidence: 77%
“…Maternal PPD symptoms (EPDS !10) were also found to significantly affect Total Behaviour Problems (b ¼ 0.670; p < 0.001), Internalizing Problems (b ¼ 0.172; p ¼ 0.005), and Externalizing Problems (b ¼ 0.232; p < 0.001) scores in children evaluated with the Child Behavior Checklist (CBCL) at 3 months postpartum 30 . A similar association was found between PPD symptoms and child behavioral outcomes in another study, with significant associations between PPD symptoms as measured by the CES-D and child behavioral problems as measured by the Behavior Problems Index (BPI; p < 0.0001) 38 . Two studies reported non-statistically significant associations between PPD symptoms and outcomes in children, such as infant development (cognitive, language, and motor) at 18 months 29 and cognitive function at 24 months of age 74 .…”
Section: The Humanistic Burden Of Postpartum Depressionsupporting
confidence: 77%
“…When multiple stress factors are present such as poverty and preterm birth, protective factors such as sensitive and responsive parenting can help in the development of early resiliency in children (Bradley et al, 1994). Maternal depression can directly impact child behaviour, an effect more pronounced with low maternal education, fewer assets and indigenous ethnicity (Flynn et al, 2017). The importance of maternal wellbeing in early childhood stimulation has been well‐recognized by the WHO (Daelmans et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, home environment is shown to mediate the effect of or exert more influence than SES on child development (Coscia et al, 2001; Ferreira, Godinez, Gabbard, Vieira, & Caçola, 2018; Lohndorf, Vermeer, Carcamo, & Mesman, 2018; Ronfani et al, 2015), making it a proxy marker for early childhood care and education (Iltus, 2006). In addition, maternal factors including cognition, education and depression can impact child cognition, not only through genetic factors but also by optimizing the relational environment (Andrade et al, 2005; Bradley, Corwyn, Burchinal, McAdoo, & García Coll, 2001; Bradley, Corwyn, McAdoo, & García Coll, 2001; Flynn, Chung, Ozer, & Fernald, 2017; Pachter, Auinger, Palmer, & Weitzman, 2006; Ronfani et al, 2015). Maternal self‐esteem also affects the home environment, as shown in a study from Andhra Pradesh, India (Fernandez, Vazir, Bentley, Johnson, & Engle, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The main finding of this study was that, considering child characteristics as confounding variables, children of mothers with moderate and severe depressive symptoms were less likely to regulate their emotions and behaviors, whereas when considering maternal and housing characteristics, the association held when mothers had severe depressive symptoms. Studies in diverse populations in Pakistan, Finland, Canada, United States, Mexico, and Australia reported that maternal depression was negatively associated with children's emotion and behavior regulation ( Urizar and Muñoz, 2021 , Herba et al, 2013 , Conroy et al, 2012 , Liu et al, 2017 , Tuovinen et al, 2018 , Giallo et al, 2018 , De Oliveira et al, 2019 , Flynn et al, 2017 ). In contrast to high-income countries, countries with limited economic resources present social and economic factors that could contribute to this association such as low socioeconomic status of the mother at the time of pregnancy that persists until after delivery (leading to food insecurity), poor parental stimulation, intimate partner violence, child abuse and negative social situations that produce an unsafe environment for child and maternal development, making it difficult for adequate self-regulation of children's emotions and behavior ( Harris and Santos, 2020 , Lovejoy et al, 2000 , Palermo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%